EFFORTS TO IMPROVE WORK DISCIPLINE AND ISLAMIC WORK ETHICS WITH WOMEN'S LEADERSHIP ROLES: EFFORTS TO IMPROVE WORK DISCIPLINE AND ISLAMIC WORK ETHICS WITH WOMEN'S LEADERSHIP ROLES - Musoli Musoli; Seto Satriyo Bayu Aji (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The purpose of this research is to empirically study employee perceptions of their work in working in micro, small and medium enterprises (MSMEs). The research design uses a quantitative approach through research instruments. The unit of analysis in this study is MSME employees in Yogyakarta who have worked for at least 1 year. Data were collected through face-to-face distribution by researchers with Purposive sampling technique was used to collect this research sample. The total respondents in this study are 138 who are employees of MSMEs in the Special Region of Yogyakarta. This study shows that female leadership has a significant positive effect on Islamic work ethics. The empirical findings also show a significant positive effect of female leadership on work discipline and Islamic work ethics has a significant positive effect on work discipline.